Role of precursors on the photophysical properties of carbon nitride and its application for antibiotic degradation - Panneri, S.; Ganguly, P.; Nair, Balagopal; Mohamed, A.; Warrier, K.; Hareesh, U. (Springer, 2017)
In this paper, we provide a comprehensive evaluation of graphitic carbon nitride (C3N4) powders derived from the four different precursors melamine, cyanamide, thiourea, and urea for the photocatalytic degradation of tetracycline (TC) antibiotic under sunlight irradiation. The powders were synthesized by employing the conventional thermal decomposition method. The synthesized powders were examined using different characterization tools for evaluating the photophysical properties. The degradation profile revealed that urea-derived C3N4 showed the highest activity while melamine-derived C3N4 showed the least activity. The TC degradation efficiency of the photocatalyst was found to be influenced more by the surface area values despite extended absorption by melamine in the visible light region. Stability tests on urea-derived C3N4 and others were checked by four runs of TC degradation under sunlight irradiation. The synthesized C3N4 powders also confirmed the dominance of urea-derived powders for cyclic stability.